The Roles of Government as Stakeholder in Developing Destination in Surabaya, Indonesia (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2016)
Tourism is a fast growing industry around the globe, including in Indonesia. Report published by UNWTO in 2015, shows that the industry contributes 9 percent of the world GDP. Recently, Indonesia is taking more serious action in developing tourism industry in the country. Tourism has been set up as the biggest money spinner for Indonesian foreign revenue in the future. The goal of the Indonesian government is to achieve more than 20 million foreign tourists by 2019. Many Indonesian cities transform themselves to be a place of doing business as well as a place to visit. As the second biggest city in Indonesia, Surabaya plays important role as the hub of development for eastern part of the country. Surabaya has grown from manufacture based city into service and trade city. Tourism destination development becomes one of the important issues in Surabaya. Since2005, the use of city branding “Sparkling Surabaya”, has made the city become one of tourist destinations in East Java region. Destination development needs constant and effective support by the stakeholders. The local government has an important role in destination development. This study aims to identify the role of the government in the process of developing the destination in Surabaya. This study is done qualitatively by using in depth interview with the executives body that represented by Surabaya Tourism Office, as the primary data. The strategy and the action plan of the government are also explored in the study. The result shows that Surabaya government has an important role in destination development; by working closely with other stakeholders, such as private business and local community. This study can be used by the government as the reflection of their strategy in developing the destination. Moreover, all of the executives of Surabaya government need to have the same objectives and perspective in developing Surabaya as tourist destination in Indonesia.